Morphophysiological analysis of the salivary glands of Rhipicephalus sanguineus sensu lato (Acari: Ixodidae) exposed to ozonated water: A control strategy - Abreu, M. R. [UNESP]; Delalibera, I.; Pereira, N. R.C. [UNESP]; Camargo-Mathias, M. I. [UNESP] (Wiley, 2020)
The tick Rhipicephalus sanguineus sensu lato has great medical and veterinary importance, mainly because the ability to transmit many diseases, causing harm to pets but also risks to public health. The blood spoliation and transmission of pathogens occur because of the immunosuppressive action of these ticks' saliva, a potent mixture of bioactive substances that is secreted by the salivary glands, one of the organs responsible for their biological success, and hence the target of studies for their control. Ozone has promise for use as an alternative acaricide, due to its proven efficiency in controlling agricultural and food pests, besides posing no risk of environmental contamination or to animal and human health. Therefore, this study evaluated the acaricidal potential of exposure of females of R. sanguineus s.l. to ozonated water at many concentrations and analysed the morphophysiological alterations of the salivary glands, employing histological and light microscopic techniques. The results demonstrated that the ozonated water at the concentrations investigated caused severe alterations in the salivary glands, bringing a new perspective for control of R. sanguineus s.l., through an ecologically correct method due to the absence of harm to non-target organisms and the environment.
Keywords: control; morphology; ozone; salivary glands; ticks